A Review of the Research on the Prediction Model of Extreme Learning Machine. Issue 4 (June 2019) - Yibo, Li; Fang, Liu; Qi, Cao
Abstract: With the wide application of prediction, the research of prediction algorithm and theory has made a great progress. In recent years, extreme learning machines have been used in the field of prediction, such as stock price prediction. The prediction algorithms of ELM are reviewed in this paper, which includes the single extreme learning machine prediction algorithm and the combined prediction algorithm. At the same time, the existing problems and research directions are pointed out.